IMPROVING ECONOMIC EFFICIENCY ON DEGRADED PERMANENT MEADOWS BY VARIOUS MANAGEMENT SYSTEMS - Simona ACATRINEI (DUMITRIU); Mihai STAVARACHE; Cristian-Sorin GAVRILĂ; Elena-Manuela VACARCIUC; Ana-Maria DUDĂU; Daniela BOURUC; Elena STAVARACHE; Mir (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
The purpose of this research is to study the possibility of enhancing the multifunctionality of permanent degraded grasslands by overseeding, with special look on economic efficiency. The experience that is the subject of the research was organized in the Research and Development Station for Meadows, Vaslui area, on a Dichanthium ischaemum (L.) Roberty meadow. In the study area there are large areas of permanent meadows, at different stages of degradation, due to the positioning on surfaces with different degrees of inclination, eroded or subject to erosion process, due to abandonment or non-rational use, with an inappropriate load of animals and failure to apply maintenance or improvement measures. Due to these aspects, the production is small and the floral composition is dominated by species with medium and low fodder value. In order to increase the production of permanent grassland in the area, it was considered necessary to apply organic fertilizers, and their effect was compared to that of abandonment, mulching or simple use, and with overseeding measures. Biological material used (a mixture of: 70% Bromus inermis Leyss. + 30% Onobrychis viciifolia Scop. - 30 kg·ha-1 + 25 kg·ha-1). Total expenses, net income and profitability rate (rate of return) were calculated. The lowest costs were recorded when the biomass was only harvested, no other action being performed. When overseeding and fertilization were overlapping the costs were the highest, the economic efficiency being carried close to zero, but more likely, the effect of fertilization has been greatly diminished due to poor climatic conditions.